The London bombings: radicalisation and its implications - Burnell, Sarah Jamie (2016)
THE investigative work continues in London under the disconcerting possibility that the coordinated bombings of July 7 were the work of British citizens. Police in London reportedly have revealed that all four suspects were British nationals of Pakistani descent, making them the first suicide bombers to strike in Europe. The methods used in the attacks, and the disclosure that the perpetrators were from within the British Muslim community, caused more surprise and shock than if the perpetrators would have entered the United Kingdom solely for this purpose - as did the 9/11 hijackers in the case of the United States.